The Republic of Belarus participation in NATO programme “Partnership for peace” (1995–2016) - Zhuravskaya, Olga S. (Journal of the Belarusian State University. International Relations, 2020)
The present article is devoted to the analysis of Belarus – NATO relations in the context of instability and turbulence of regional security. The author came to the conclusion that the main actors from the Belarusian side formulating the framework of Belarus – NATO interaction are the State Secretariat of the Security Council of the Republic of Belarus, Ministry of Defence of the Republic of Belarus, and Ministry of Foreign Affairs of the Republic of Belarus. Moreover, the major directions of Belarus – NATO relations are Individual partnership programme elaborated for two years within Partnership for peace programme, Partnership for peace planning and review process. The author evaluates the effectiveness of Individual partnership programme via demonstration of case studies and results of certain directions.